The Importance of the Code of Ethics in Preventing Fraud for the Professional Accountant - Andri Goklas; Arifin Hasudungan Manurung (Jurnal Economic Resource, 2022)
The development of accounting science which aims to present company financial information can turn out to be fraudulent. Cases of corporate financial scandals, such as KAP Andersen and Enron and KPMG-Siddharta & Harsono, manipulated by accountants can cause losses to much parties Research with literature study is research that uses sources and data collection methods by taking data in the library, then reading, taking notes, and processing research materials. For this reason, the code of ethics in the accounting profession is important. This study discusses the importance of a code of ethics in preventing fraud in the accounting profession with a literature study approach. The results show that the code of ethics is important because it can embed professional values and ideals and increase public trust.